Dermal Filler - Mawu, Ferra O. (UNIVERSITAS SAM RATULANGI, 2018)
Abstract: Dermal filler is a non-surgical procedure to improve facial volume or the anatomy of other parts of the body. It is also a rejuvenate therapy to achieve a younger appearance. Besides that, the need of lipodystrophy therapy is increasing. There are several types of fillers with their superiorities and inferiorities; therefore, it is pretty difficult to determine and choose the ideal filler. Dermal fillers vary in duration of therapeutic effect, filler technique, filler origin, and their physical properties. To date, there is no perfect filler so far. An ideal filler must be non-allergenic, non-carcinogenic, non-teratogenic, as well as has achievable cost and long acting effect. In case that dermal filler is therapeutical indicated, good preparation of doctor and patient is essentially needed. Consultation and information have to cover the therapy indication, filler technique, filler limitation, side effects, outcome, cost, and informed consent. As the other cosmetic procedures, to achieve optimal satis-faction, the doctor must be able to provide effective communication to the patient before and after the dermal filler therapy.Keywords: dermal fillerAbstrak: Dermal filler adalah prosedur non-bedah untuk penambahan volume wajah atau anatomi tubuh lainnya. Prosedur ini juga merupakan salah satu terapi rejuvenasi yang bertujuan untuk tampilan lebih muda. Selain itu, kebutuhan untuk terapi lipodistrofi juga makin meningkat. Terdapat berbagai jenis filler dengan keunggulan dan kekurangaood prepnnya masing-masing, sehingga agak sulit menentukan atau memilih produk filler yang ideal. Dermal filler bervariasi dalam hal lamanya efek terapi yang diperoleh, cara pemberian, asal filler, dan sifat fisiknya. Sampai saat ini tidak ada produk filler yang sempurna. Untuk menjadi ideal, produk filler harus nonalergenik, nonkarsinogenik, nonteratogenik, harga terjangkau dan berefek terapi yang panjang. Saat dermal filler menjadi pilihan terapi atau tindakan, persiapan yang tepat baik dokter maupun pasien merupakan hal yang esensial. Konsultasi dan informasi harus meliputi ketepatan indikasi pemberian filler, tehnik pemberian, keterbatasan filler, efek samping, kemungkinan hasil akhir, biaya, dan informed consent. Sebagaimana prosedur kosmetik lainnya, untuk kepuasan bersama, dokter harus mampu dan bersedia memberikan komunikasi efektif kepada pasien sebelum dan sesudah terapi dermal filler.Kata kunci: dermal filler